Medium-term Oil Supply Outlook in the Middle East and North Africa - Bassam Fattouh; Bill Farren-Price (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2020)
This issue of the Forum looks at the medium-term oil supply outlook in the Middle East and North Africa. Middle East and North Africa (MENA) oil producers are expected to increase oil production capacity by 5.7 per cent over the next five years (up to 2025), to 33.5 million barrels per day (mb/d) from the current 31.7 mb/d, this Forum's survey of regional producers' upstream planning shows. All growth estimates are predicated on political and fiscal stability and current expansion plans by governments and international oil companies (IOCs) and are therefore subject to change and potential underperformance. But a realistic best-case scenario for the selected countries shows capacity growth led by the UAE, itself able to deliver 0.6 mb/d of growth over the outlook period, while Libya and Kuwait increase by 0.5 mb/d and Iraq by 0.3 mb/d. The growth more than offsets modest capacity declines for some of the smaller regional producers, especially where those countries have chosen to switch their focus away from sustaining crude oil output in favour of gas and unconventional hydrocarbons development. Of course, the impact of sanctions, years of underinvestment due to civil war, poor sectoral management and (where applicable) present and future OPEC production policies will all continue to weigh heavily on growth prospects. The highest potential growth country, Iraq, is characterized by high security and political risk and it is for that reason that it is not the leading growth prospect. This conservative forecast still acknowledges that Baghdad has been able to successfully expand its upstream sector, despite the political tensions between regions and the federal government, and despite years of civil war in the north of the country. In the same way, Libya's civil war has for periods disrupted the recovery of the oil sector and forced the suspension of oilfield operations and exports. But these interruptions have been the exception rather than the rule and, in a best-case scenario, Libya's National Oil Corporation should be able to continue to expand production from existing fields over the medium term, restoring pre-2011 capacity levels.
Keywords: 330